Manajemen Pendidikan Aqidah Akhlak MTs Al Munawwarah di Lingkungan Eks Lokalisasi Pekerja Sex Komersial (PSK) Desa Slarang Kecamatan Kesugihan Kabupaten Cilacap - Sudadi Sudadi (LPPM IAINU Kebumen, 2022)
The purpose of this study is to describe the management of MTs The Impact on Students Who Come from the Ex-Localization of Slarang Commercial Sex Workers (PSK) in the 2019/2020 Academic Year. This research was conducted with a qualitative approach. The subjects of this study were the principal, teachers, and students. Data collection techniques from this study using the method of observation, interviews, and documentation. The results of this study indicate that, 1) Learning planning by teachers is carried out by compiling annual programs, semester programs, developing learning syllabus, and developing lesson plans. 2) Organizing learning is carried out by the teacher, namely: structuring classrooms, structuring students, using learning resources, using learning media, and using facilities and infrastructure. 3) Implementation of learning is the teacher carrying out learning activities including preliminary activities, core activities, and closing activities. 4) Learning evaluation is the principal of madrasah providing guidance, assistance, supervision and assessment on problems related to the technical implementation and development of teaching education in the form of improving teaching education programs and activities to create teaching and learning situations. Meanwhile, the teacher evaluates learning through process assessment and results assessment. Process assessment is carried out on student participation both individually and in groups during the learning process. Assessment of results is carried out at the middle and end of the semester. 5) Reporting of learning outcomes that the content of reporting learning outcomes includes things such as student learning profiles at madrasah (academic, physical, social and emotional), student participation in activities at madrasah (active, moderate, insufficient or inactive), progress of results student learning during a certain learning period, appeal to parents.